A Brief Propensity Index for Conduct Disorder (BPI-CD): Development, Validity and Reliability - Oguntayo, Rotimi; Olaseni, Abayomi, Oladele; Miracle, Kehinde; Helen, Osinowo; Isaac, Yakubu, Isaa (My University, 2020)
Conduct Disorder (CD) can pose serious concerns to parents, home and the society, meanwhile assessing this construct in clinical practice has been based on western concepts which limited the cultural factors implicated in CD. This study presents a reliable and valid screening tools for conduct disorder among juveniles and general population respectively. Existing scales that assessed deviant behavior or CD were reviewed. A qualitative study was conducted using juveniles and college students between the age 10 to 19; this is to determine salient constructs related to CD. Themes were generated, and those related to specific predictors of CD were used to generate a 17-item of Brief Propensity Index for Conduct Disorder (BPI-CD). A cross-sectional survey was then conducted among 125 juveniles and college students to assess the reliability and validity of the scale. The participants were purposively selected. Construct validity using exploratory factor analysis was factored and Varimax rotated the scale into six components (KMO = .685, df=171, p<.001). Convergent validity results showed a significant relationship between BPI-CD and Youth Deviant Behavior Variety Scale (r=.338, p<.01), while discriminant validity results revealed a non-significant relationship between (BPI-CD) and Social Skills Scale (r=.101, p>.05), thus showing a strong validity. The reliability dimensions and subscales have meritorious reliability (Aggression to People/Animals, α =.76, Serious Violation of rule and destruction of property, α =.73; Deceitfulness and theft, α =.68). The overall Cronbach’s Alpha was 0.86. BPI-CD is therefore recommended as reliable and valid screening tool for conduct disorder tendency.
Keywords: Adolescents; Brief Propensity Index for Conduct Disorder; Delinquencies; Juveniles